Nuances da correção: uma análise sobre a escrita acadêmica - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The present work seeks, based on textual linguistics, normative grammar and theory of enunciation, to analyze, based on the textual choices materialized in the statements of monographic course conclusion works (TCCs), the adjustments and inadequacies observed in five distinct areas of knowledge, namely: Agricultural Engineering, Electrical Engineering, Administration, Journalism and Nursing, in orderto collaborate with the study of academic writing. In this way, we will carry out an analysis that basically starts from two textuality criteria: cohesion and coherence, using, predominantly, Antunes (2009) who explains the textual relationships frequently seen in texts. Based on these two criteria, we also try to reflect on Grammar and Enunciation. We highlight, among the main findings of the study, issues related to cohesion, intertextuality, locution and enunciation, considered as characteristics of the monographic TCC genre.
Keywords: Coesão; Coerência; Gramática normativa; Escrita acadêmica; Linguística textual; Cohesion; Coherence; Normative grammar; Academic writing; Textual linguistics; CNPQ::LINGUISTICA, LETRAS E ARTES